Development of a Temperature and Humidity Monitoring Website for the Lembang Agri Greenhouse - Maulana, Keindra Bagas; fani, Junior Al; Alam, Bramantio Syahrul; Hartawan, Liman; Rakhmat, Galih Ashari (Institut Teknologi Nasional, Bandung, 2025)
Institut Teknologi Nasional Bandung (Itenas), in collaboration with Gapoktan Agri Lembang, has developed a web-based monitoring system to help farmers adapt to climate change. The system tracks temperature and humidity in real-time, allowing farmers to take quick actions. It uses technologies like Laravel, Firebase, and data visualization tools such as Chart.js and Plotly.js. The system integrates sensors to measure temperature and humidity, sending data to a server accessible through a web platform, updating every 15 minutes. When implemented in Gapoktan Agri Lembang's greenhouse, local farmers positively responded to the technology, recognizing its potential to improve greenhouse management. This system aims to enhance the efficiency and productivity of horticultural farming in Lembang and serves as a model for adapting agriculture to climate change.